2017
DOI: 10.1098/rsos.171161
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and fluorescent probes for real-time naked eye sensing of copper ion in solution and on paper substrate

Abstract: In this paper, BT ((E)-2-(4-(4-(bis(pyridin-2-ylmethyl)amino)styryl)-3-cyano-5,5-dimethylfuran-2(5H)-ylidene)malononitrile) with strong donor–π-acceptor structure was synthesized, which showed both colorimetric and fluorescent sensing ability toward Cu2+ with high selectivity and sensitivity. Job plot and mass spectra measurement revealed a 1 : 1 coordination mode between Cu2+ and probe BT in ethanol/HEPES (1 : 4 v/v) buffer (pH 7.2) solution, and the binding constant was calculated to be 3.6 × 104 M–1. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…− However, Ru‐L in presence of Cu 2+ ion was substantially sensitive to both acidic as well as basic pH. The emission intensity of Ru‐L–Cu increased obviously at low pH (5.0‐3.0), due to the competition between the H + and Cu 2+ ions . On further increase of the pH, the emission intensity almost remained constant up to pH 9.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…− However, Ru‐L in presence of Cu 2+ ion was substantially sensitive to both acidic as well as basic pH. The emission intensity of Ru‐L–Cu increased obviously at low pH (5.0‐3.0), due to the competition between the H + and Cu 2+ ions . On further increase of the pH, the emission intensity almost remained constant up to pH 9.0.…”
Section: Resultsmentioning
confidence: 99%
“…A di‐(2‐picolyl)amine (DPA) moiety was tethered to the phenanthro‐imidazole unit via a phenyl‐CH 2 linker. DPA moiety linked with a fluorophore has already been reported as a promising binding site to Cu(II) with good selectivity However, in most of the cases, the detection was performed either in neat organic or organic‐water solvent systems and rarely reported in fully aqueous medium.…”
Section: Introductionmentioning
confidence: 95%
“…Too acidic environment may protonate the pyrrole moiety, which reduces the coordination ability, and too basic environment may reduce the free Co 2+ ions in solution and influence the sensitivity. 59…”
Section: Results and Discussionmentioning
confidence: 99%
“…These results demonstrated that the fluorescence intensity of probe 1 was effectively enhanced by UO 2 2+ with such a metal ion as the background. Thus, probe 1 exhibits excellent selectivity for UO 2 2+ except for Ca 2+ and Rb + …”
Section: Methodsmentioning
confidence: 94%